2011
DOI: 10.1096/fj.11-180679
|View full text |Cite
|
Sign up to set email alerts
|

The cysteines of the extracellular loop are crucial for trafficking of human organic cation transporter 2 to the plasma membrane and are involved in oligomerization

Abstract: Human organic cation transporter 2 (hOCT2) is involved in transport of many endogenous and exogenous organic cations, mainly in kidney and brain cells. Because the quaternary structure of transmembrane proteins plays an essential role for their cellular trafficking and function, we investigated whether hOCT2 forms oligomeric complexes, and if so, which part of the transporter is involved in the oligomerization. A yeast 2-hybrid mating-based split-ubiquitin system (mbSUS), fluorescence resonance energy transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 45 publications
(56 reference statements)
3
57
0
Order By: Relevance
“…Consistent with the near loss of membrane expression, the J max value associated with MPP transport by the C89A and C103A mutants, both of which supported modest MPP transport, was reduced ϳ15-to 25-fold. These data are in agreement with those of Brast et al (2), who used a green fluorescent protein-tagged construct of hOCT2 to show by immunocytochemistry that single loop cysteine mutants are largely retained in the cytosol of HeLa SS6 cells. Plasma membrane expression of mouse Oat1 at the plasma membrane of HeLa cells was also reduced following mutation of conserved cysteine residues in its long extracellular loop (24).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the near loss of membrane expression, the J max value associated with MPP transport by the C89A and C103A mutants, both of which supported modest MPP transport, was reduced ϳ15-to 25-fold. These data are in agreement with those of Brast et al (2), who used a green fluorescent protein-tagged construct of hOCT2 to show by immunocytochemistry that single loop cysteine mutants are largely retained in the cytosol of HeLa SS6 cells. Plasma membrane expression of mouse Oat1 at the plasma membrane of HeLa cells was also reduced following mutation of conserved cysteine residues in its long extracellular loop (24).…”
Section: Discussionsupporting
confidence: 92%
“…OCT2 belongs to a larger family of solute carriers (OCT family), which include other OCTs (OCT1 and OCT3), the "novel" organic cation transporters 1-3 (OCTN1-3), and the organic anion transporters [1][2][3][4][5]. OCT family members have several structural features in common, including 12 putative transmembrane spanning helices (TMHs), intracellular COOH and NH 2 termini, a large extracellular loop between TMHs 1 and 2, and a large intracellular loop between TMHs 6 and 7.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Disulfide bonding on the surface of the human organic cation transporter 2 and the Cys-loop ligand-gated ion channel receptors was shown to have critical functional roles (20,21). Our functional assay showed that presence or absence of the two disulfide bonds in EL-3 had no demonstrable effect on NBCe1-A base transport, indicating that in the heterologous expression system the two disulfide bonds in EL-3 do not affect the baseline NBCe1-A base transport activity.…”
Section: Discussionmentioning
confidence: 74%
“…The N-glycosylation of EL-3 is predicted to be important for NBCe1-A plasma membrane trafficking, whereas the role of the 4 highly conserved cysteines in EL-3 has remained unclear. In the human organic cation transporter 2, cysteines in the extracellular loops play a crucial role in protein plasma membrane trafficking and are involved in transporter oligomerization (20). Moreover, in Cys-loop ligand-gated ion channel receptors, the disulfide bonds in a large extracellular loop are involved in forming the substrate interaction site (21).…”
mentioning
confidence: 99%